The nonlinear optical properties of Epoxy/Alumina Nanocomposites - Wheeb, Ahmed H.; Mahdi, Zainab F.; Faris, Rawaa A. (Iraqi Journal of Laser, 2019)
Linear and nonlinear optical properties of epoxy/ Al2O3 nanocomposites system were studied for epoxy neat and (0.5, 1.5, 3, and 5) % Al2O3 nanocomposites.The band gap of epoxy and its nanocomposites was obtained at these weight ratios. Nonlinear optical properties experiments were performed using Q-switched Nd:YAG laser z-scan system.These experiments were carried out for different parameters: wavelengths (1064 nm and 532 nm), laser intensities (0.530, 0.679, and 0.772) GW/cm2 and weight ratio of Al2O3 nanocomposites. The results showed that the band gaps were decreased with increasing the weight ratio of nanoalumina except at 5wt% and the nonlinear refractive index coefficient is directly proportional to the incident intensities while opposite for the nonlinear absorption coefficient. Different types of nonlinear absorption coefficients were given .One, two and three photons absorption according to band gap and laser photon energy were appeared. So that epoxy/ Al2O3 nanocomposites can be used as a promising nonlinear device.